DEVELOPMENT AND COST ANALYSIS OF A NEW IBS SYSTEM - CHIN, KAREN MAY LIN (Universiti Teknologi PETRONAS, 2021)
Conventional in-situ construction has indeed been one of the most common construction methods till date, and is being adopted in most of the construction projects in Malaysia. Despite its familiarity among designers, contractors and labours, there are many disadvantages of it, including time consuming, labour intensive, dangerous site condition and many more. Cost and time overrun due to the usage of unskilled foreign worker proves the need of shifting to a more organized method of construction, which is the Industrialized Building System (IBS).